Ligand Variations in New Sulfonamide-Supported Group 4 Ring-Opening Polymerization Catalysts - Schwarz, A; Herbert, K; Paniagua, C; Mountford, P (2010)
The synthesis, structures, and ring-opening polymerization (ROP) capability of a wide range of sulfonamide-supported group 4 amide, alkyl, and alkoxide complexes, varying in sulfonamide N-substituent, metal, coordination number, and geometry, are reported. Reaction of Ti(NMe 2) 4 or Ti(NMe 2) 2(O iPr) 2 with MeOCH 2CH 2N(CH 2CH 2NHSO 2Me) 2 (12, H 2N 2MsN OMe) or PhCH 2N(CH 2CH 2NHSO 2R) 2 (R = Tol (10, H 2N 2TsN Ph) or Me (11, H 2N 2MsN Ph)) afforded Ti(N 2MsN OMe)(NMe 2) 2 (18), Ti(N 2TsN Ph)(NMe 2) 2 (19), Ti(N 2MsN Ph)(NMe 2) 2 (20), Ti(N 2MsN OMe)(O iPr) 2 (21), Ti(N 2TsN Ph)(O iPr) 2 (22), Ti(N 2MsN Ph)(O iPr) 2 (23), and Ti(N 2TsN Ph)(O iPr)(NMe 2) (24). Reaction of N(CH 2CH 2NHSO 2R) 3 (R = Tol (13, H 3N 3TsN), Me (14, H 3N 3MsN), or Ar F (15, H 3N 3ArFN, Ar F = 3,5-C 6H 3(CF 3) 2)) with Zr(CH 2SiMe 3) 4 formed Zr(N 3RN)(CH 2SiMe 3) (R = Ts (30), Ms (31), or Ar F (32)). Reaction of 15 with Zr(NMe 2) 4 gave Zr(N 3ArFN)(NMe 2) (33). Complexes 19, 21, 24, 30, 32, and 33 were crystallographically characterized. Monomeric six- or five-coordinate structures were found for the titanium complexes 19, 21, and 24, whereas the zirconium alkyls 30 and 32 were dimeric in the solid state with terminal and bridging κ 2(N,O)-bound sulfonamides. Complexes 18-24 and 30-33, the previously reported Ti(CyN 2R)(O iPr) 2 (25 or 26; CyN 2R = 1,2-C 6H 10(NSO 2Tol) 2 or 1,2-C 6H 10(NSO 2Mes) 2), and in situ generated isopropoxide initiators derived from 30-32 were investigated for the ROP of ε-caprolactone (ε-CL). The four-coordinate 25 was the most active, forming poly(ε-CL) with a relatively narrow PDI and well-controlled M n. Compounds 22, 23, 25, and 26 and isopropoxides generated in situ from 30-32 were all active for the ROP of rac-lactide. Of these, the initiators based on Zr(N 3RN)(CH 2SiMe 3) (30-32) with iPrOH co-initiator gave good activities and excellent PDIs (1.08-1.11) and agreement between measured and predicted M n. © 2010 American Chemical Society.